Linear relationship between potential and concentration in flow potentiometry - Neto, José Anchieta Gomes [UNESP]; Zagatto, Elias Ayres Guidetti (My University, 2000)
In potentiometric-flow systems, linear-potential responses for logarithmic concentrations can be attained for first-(or pseudo-first-) order reactions in which the monitored chemical species react with the analyte during a fixed time interval. To demonstrate this property, the determination of glycerol based on its oxidation by periodate and potentiometric monitoring of the remaining periodate was selected. Influence of reagent concentration and timing on the linearity of the analytical curve were investigated. A mathematical treatment was derived, and potentialities/limitations of the approach were outlined. The system was applied to analysis of soap and lixivia samples. The analytical curve within 200 and 2000 mg L-1 (r = 0.99975; n = 5) was described as E = 8.166+0.0478 [glycerol]. The sample throughput was 100 h-1, and a measurement repeatability within 0.5 mV was always observed. By applying a t-test, there was no statistical difference between the results obtained by the proposed procedure and by iodimetric titration at the 95% confidence level.